Adiscourse-pragmatic oriented approach to printer's drama : trouble in the works betrayal and mountain language - OUALI, Farida (University of Mostaganem, 2015)
The present paper is an application of a discourse-pragmatic oriented approach to Pinter’s drama. In this study, the theories of pragmatics and discourse analysis are applied to Pinter’s three plays: Trouble in the Works, Betrayal and Mountain Language. The aim of the first analysis is to investigate the pragmatic theories and particularly the cooperative principles of Grice. The second analysis displays the strategic manipulation of language for showing what is socially appropriate, and hence, Brown’s and Levinson’s theory of politeness is tackled. In the last play, a critical discourse analysis is applied to Pinter’s political text. After having investigated the structure of verbal interaction and assessed the strategies that speakers and hearers use in conversations taken from the three plays, the findings of the present enquiry first demonstrate the importance of the cooperative principles in accounting for the absurdity of the play. Second, they illustrate how participants manipulate their use of language under the restriction of context, social distance and relative power, and finally, they exhibit the role of language and language use in the reproduction of dominance and inequality